Enhancer and silencerlike sites within the transcribed portion of a Ty2 transposable element of Saccharomyces cerevisiae. - Farabaugh, P (1989)
The Ty2-917 element is a member of the Ty2 class of retroviruslike transposable elements of Saccharomyces cerevisiae. We showed that regions downstream of the Ty2-917 transcription start site modulate its transcription. One region was located downstream of the transcription initiation site (position 240) and within the first 559 base pairs of the element. This region had a dramatic effect, causing an approximately 1,000-fold increase in steady-state levels of RNA. The region stimulated transcription when placed in either orientation upstream of a heterologous gene, HIS4, lacking its own upstream activation sequence (UAS). We termed this positively acting region an enhancer, by analogy to sites described in higher cells, to distinguish it from yeast UASs which do not function when placed within the transcribed portion of the gene. Though, like some higher eucaryotic enhancers, the Ty2-917 enhancer is located within the transcribed region, it is unlike them in that it occurs within a coding region rather than in an intron. The Ty2-917 enhancer and the Ty2-917 UAS had a synergistic effect on transcription, together stimulating transcription 15-fold over the predicted additive effect. We also identified a site which decreases RNA accumulation, located about 750 base pairs into the element. This site functioned in only one orientation when inserted upstream of the UAS-less heterologous gene. The site was similar to silencers, or negative enhancers, in that it acted to repress transcription from outside the transcribed region, but was distinct in that the function of a canonical silencer was independent of orientation.